Preparing Pre-service Teachers for Teaching Post-Pandemic: Reflections on How to Adapt Microteaching - Kelly R. Maguire (Journal of Scholarly Engagement)
The purpose of this reflective practice was to explore the unexpected revelation that following the completion of my doctoral journey during the pandemic, my future teaching approach would need to change. The identified problem was the unexpected revelation that I did not know how I would adapt microteaching to prepare my pre-service teachers for teaching post-pandemic with the subsequent push to teach online. The following are the proposed reasons for the problem: (a) education changed instantaneously, and (b) I was unprepared. In evaluating the reasons, the issue of adapting microteaching to an online modality such as Zoom was one necessary outcome from the reflective practice. Future research is recommended to explore how educators who instruct in teacher preparation programs can continue to use microteaching both in traditional university classrooms and online modalities such as Zoom.